Scientometrics Study of Research productivity of Delhi University (DU), Jamia Millia Islamia (JMI) and Jawaharlal Nehru University (JNU) , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Scientometrics studies have now a days become popular to evaluate and rank research productivity of authors, institutions and universities globally. Number of such studies has been published in various journals, conference proceedings, review papers, book chapters, and research reports. The study was taken to analysis research productivity of University of Delhi, Jamia Millia Islamia and Jawaharlal Nehru University during the last 30 years.